The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/md17050305
|View full text |Cite
|
Sign up to set email alerts
|

Actinomycin V Inhibits Migration and Invasion via Suppressing Snail/Slug-Mediated Epithelial-Mesenchymal Transition Progression in Human Breast Cancer MDA-MB-231 Cells In Vitro

Abstract: Actinomycin V, an analog of actinomycin D produced by the marine-derived actinomycete Streptomyces sp., possessing a 4-ketoproline instead of a 4-proline in actinomycin D. In this study, the involvement of snail/slug-mediated epithelial-mesenchymal transition (EMT) in the anti-migration and -invasion actions of actinomycin V was investigated in human breast cancer MDA-MB-231 cells in vitro. Cell proliferation effect was evaluated by 3-(4,5-Dimethylthiazol)-2,5-diphenyltetrazolium bromide (MTT) assay. Wound-hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 32 publications
0
27
0
Order By: Relevance
“…We seeded the cells on glass over slips and treated them with 0 to 8 μmol/L Ivalin for 24 h. Immunofluorescence staining was performed as previously described [17].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We seeded the cells on glass over slips and treated them with 0 to 8 μmol/L Ivalin for 24 h. Immunofluorescence staining was performed as previously described [17].…”
Section: Methodsmentioning
confidence: 99%
“…We exposed the cells to indicated concentration of Ivalin for 24 h, then the protein expressions were analyzed by Western blotting which we carried out as previously described [17].…”
Section: Methodsmentioning
confidence: 99%
“…The cells were treated with serial concentrations of Act V and Act D (0–0.02 μM) for 48 h, and the IC 50 s were determined (Act D, which has been used for a long time in clinic, serves as a positive control here), as shown in Table 1 and our previous study [ 10 , 11 ]. Act V exhibited considerably stronger efficacy against cancer cells with a ten-fold lower IC 50 value compared to Act D. Act V and Act D induced cytotoxicity in human normal liver LO-2 and human embryonic kidney 293T cell lines in a concentration-dependent manner ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…[ 1 ], has a similar structure to that of Act D ( Figure 1 ). In our previous studies [ 10 , 11 ], Act V was found to be more cytotoxic to tumor cells than Act D. Moreover, Act V inhibited the migration and metastasis of breast cancer cells. In this aspect, Act V may be a potential substitute for Act D, so understanding the toxicological mechanisms of Act V and Act D is of great worth.…”
Section: Introductionmentioning
confidence: 92%
“…[53] Afterward, the absorption of samples was read at 570-nm wavelength using a microplate reader (model 680; Bio-Rad Laboratories, Hercules, CA). [54][55][56][57] 2.7 | Medium H 2 O 2 assay H 2 O 2 detection was done in the control group (without any treatment) after direct-plasma treatment on Hela cells and PAM treatments (5-min treatment with both methods [the best results] and with He + 0.5% O 2 [the best combination]) and the medium was immediately (<1 min) provided using a fluorimetric hydrogen peroxide assay kit (MAK165-1KT; Sigma-Aldrich) according to manufacturer's standard protocol. At each measurement, 50 μl of the medium was collected and transferred to a flat-bottomed 96-well plate.…”
Section: Mtt Assaymentioning
confidence: 99%